Differentiated Curriculum Model at Insan Sejahtera Sumedang Integrated Islamic Middle School - Saptorini, Endang; Uswatiyah, Wiwi (Transformasi Manageria Journal of Islamic Education Management, 2025)
This paper aims to examine the theoretical concept of differentiated curriculum and its application at Insan Sejahtera Integrated Islamic Junior High School (SMPIT-IS) located in Sumedang Regency. The discussion of this junior high school curriculum is from the perspective of child development. The conclusion of the theoretical study is that Insan Sejahtera Integrated Islamic Junior High School implements the Merdeka Mandiri Berbagi Curriculum with differentiated learning that is able to develop talents, skills and innovations so that they become drivers of goodness in their environment. The teacher competency development program and the involvement of school partners in learning packaged using I-SMART technology produce independent Islamic characters who are responsible for their environment, in addition to achievements in academic and non-academic fields. Keywords: Differentiated curriculum, Independent Curriculum, SMPIT-IS curriculum program